2018
DOI: 10.1097/01.aog.0000533073.18359.b2
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Assessment and Screening Barriers for Breast Cancer in the Arab American Community [17M]

Abstract: INTRODUCTION: Breast cancer is the most common malignancy afflicting women, with an estimated 1 out in 8 U.S. women diagnosed during their lifetime. Screening for breast cancer can reduce mortality through early cancer detection. Lack of knowledge is an important barrier leading to low screening rates. Given that the Arab American population has grown approximately 47% since 2000, this study was designed to assess breast cancer knowledge and screening barriers in an Arab American community. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Ayyash et al (2018) found that 56% of the study participants (n = 175) had a mammogram in the past 2 years. Lack of insurance, absence of symptoms, and family history were reported as barriers to BC screening in AAW, in additon to lack of knowledge, fear of being diagnosed with cancer, fear of possible discomfort in the BC screening procedures, lack of doctor's recommendations, and embarrassment (Arab American Institute, n.d.; Arshad, Williams, Mabiso, Dey, & Soliman, 2011;Ayash et al, 2011;Ayyash et al, 2018;Kawar, 2013;Padela et al, 2015;Schwartz, Fakhouri, Bartoces, Monsur, & Younis, 2008;.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Ayyash et al (2018) found that 56% of the study participants (n = 175) had a mammogram in the past 2 years. Lack of insurance, absence of symptoms, and family history were reported as barriers to BC screening in AAW, in additon to lack of knowledge, fear of being diagnosed with cancer, fear of possible discomfort in the BC screening procedures, lack of doctor's recommendations, and embarrassment (Arab American Institute, n.d.; Arshad, Williams, Mabiso, Dey, & Soliman, 2011;Ayash et al, 2011;Ayyash et al, 2018;Kawar, 2013;Padela et al, 2015;Schwartz, Fakhouri, Bartoces, Monsur, & Younis, 2008;.…”
mentioning
confidence: 97%
“…Since Arab American Women (AAW) have traditionally been classified as White, they have been combined with other non-Hispanic Whites and nonmultiracial groups in survey data; therefore, their unique health status is masked. Although the AA population has been growing in number, Arab immigrants were identified to have had fewer tests for cancer early detection; Arab women in the United States have been recognized as an ethnic group that needs future research to promote their participation in BC screening (Ayyash et al, 2018;Kawar, 2013;Salman, 2012). Ayyash et al (2018) found that 56% of the study participants (n = 175) had a mammogram in the past 2 years.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This may be attributed to the acculturation factor since length of stay and integrating into the Western culture provide women an opportunity to become more familiar and knowledgeable about breast cancer screening (Badr et al 2018;Padela et al 2015). Additionally, living longer in an advanced country, such as the United States, may increase proficiency in English which provides an opportunity for these women to navigate and access healthcare services more easily (Ayyash et al 2018). Acculturation, length of stay, and English proficiency were found to be significant variables in managing health in Arab women living in the Western world (Ayyash et al 2018).…”
Section: Prevalence Of Breast Cancer Screening In Arab Countriesmentioning
confidence: 99%
“…Additionally, living longer in an advanced country, such as the United States, may increase proficiency in English which provides an opportunity for these women to navigate and access healthcare services more easily (Ayyash et al 2018). Acculturation, length of stay, and English proficiency were found to be significant variables in managing health in Arab women living in the Western world (Ayyash et al 2018).…”
Section: Prevalence Of Breast Cancer Screening In Arab Countriesmentioning
confidence: 99%